Pengaruh Pemberian Fermentasi Limbah Sawi (Brassica pekinensia L.) dalam Ransum terhadap Produksi Karkas Ayam Broiler - Laray, Linda Maria; N. G. A. Mulyantini S.S; Suryatni, Ni Putu F. (Animal Agricultura, 2025)
The purpose of this study was to analyze the effect of fermenting mustard greens (Brassica pekinensia L.) waste in rations on carcass production of broiler chickens. This study used 96 broiler day old chick (DOC) strain 707 produced by PT Charoen Pokphan Indonesia. The research method used was a Completed Randomized Design (CRD) with 4 treatments and 6 replications, each replication consisting of 4 chickens. The treatment given consisted of R0: 100% commercial feed, R1: 92.5% commercial feed + 7.5% fermented mustard greens waste, R2: 85% commercial feed + 15% fermented mustard greens waste, R3: 77.5% commercial feed + 22.5% fermented mustard greens waste. The parameters studied were carcass weight, carcass percentage, non-carcass percentage, and abdominal fat. The results of statistical analysis showed that treatment had a significant effect (P<0.05) on carcass weight, non carcass percentage and abdominal fat but had no significant effect (P>0,05) on carcass percentage. It was concluded that providing fermented mustard greens waste up to a level of 22.5% in the ration could reduce carcass weight, carcass percentage, non-carcass percentage and abdominal fat percentage